El control al poder de reforma constitucional: la acción pública de inconstitucionalidad contra los actos legislativos (2020)
The public action of unconstitutionality as well as being an importantinstrument that allows the citizen to participate in the poli ti cal life of the State,constitutes a mechanism of control in front of the parliament even when it actsunder the competence of constitutional reform. The present article presentsan introductory basis to understand the genesis, nature, characteristics andprocedural regime ofthe public action ofunconstitutionality, making a specialemphasis on the use of this mechanism against legislative acts.